2021
DOI: 10.55903/astina.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Struktur Organisasi Terhadap Kualitas Sistem Informasi Akuntansi Manajemen

Abstract: Penelitian ini meneliti pengaruh struktur organisasi terhadap kualitas sistem informasi akuntansi manajemen. Data diperoleh melalui survei dengan kuesioner. Kuesioner ditujukan kepada manajer fungsional di 24 Badan Usaha Milik Negara Indonesia di sektor Transportasi dan pergudangan. 33 kuesioner dari total 67 kuesioner (49,25%) dikembalikan dan dilengkapi.  Smart-PLS digunakan untuk pemrosesan data. Seperti yang diharapkan, struktur organisasi memiliki pengaruh signifikan terhadap kualitas sistem informasi aku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…These results are consistent with prior research that has demonstrated the influence of organizational structure on accounting information systems, as exemplified by studies conducted by (Mutaufiq, 2022), (Damanik & Fardinal, 2021), (Rosmiati & Kuraesin, 2021), and (Puspitawati, 2016).…”
Section: The Impact Of Organizational Structure On the Quality Of Acc...supporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with prior research that has demonstrated the influence of organizational structure on accounting information systems, as exemplified by studies conducted by (Mutaufiq, 2022), (Damanik & Fardinal, 2021), (Rosmiati & Kuraesin, 2021), and (Puspitawati, 2016).…”
Section: The Impact Of Organizational Structure On the Quality Of Acc...supporting
confidence: 92%
“…Evidence from previous studies supports the notion that organizational structure significantly impacts the quality of management accounting information systems in the transportation and warehousing sector of state-owned enterprises (BUMN Sektor Transportasi dan Pergudangan) (Mutaufiq, 2022). It has also been found to have a substantial effect on the implementation of accounting information systems at PT Pegadaian (Persero) Tbk (Damanik & Fardinal, 2021) and a positive influence on the quality of the accounting information system at PT.…”
Section: Organizational Structurementioning
confidence: 64%